Mixed-up about how to diagnose and treat mixed features in major depressive episodes. (8th March 2017) - Stahl, Stephen M.
Abstract : The classical point of view—that major depressive episodes (MDEs), no matter what additional symptoms are present, should be treated first line with antidepressants—is now giving way to new a notion. The idea is that MDEs mixed with a few symptoms of mania/hypomania should be viewed very differently in terms of their natural history, clinical outcome, and treatment, and perhaps certain antipsychotics should be given as first-line treatment rather than antidepressant monotherapy.